Comparative analysis of legislation in the sphere of tourism in Kazakhstan and Georgia - Kala Н.С. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2021)
A modern world is impossible without human mobility. Tourism is one of its manifestations. According to the UN and several other international organizations, tourism is an effective measure to countercultural contradictions, national enmity, as well as human poverty, an instrument for exchanging cultural traditions and experiences. This article analyses the tourism legislation of the Republic of Kazakhstan and Georgia to identify the strengths and weaknesses of such legislation and analyzes the impact of such legislation and other applied measures on the tourism industry of the country concerned. By applying the conceptual method, the international treaty base was studied within the framework of the UN World Tourism Organization. The study revealed the positive and negative aspects of the legislation in both countries, identified priority areas of tourism in such countries, and recommended the addition of existing legislation with relevant provisions that are assessed as necessary, effective, and inherent.